Expression of HSPA14 in patients with acute HIV-1 infection and its effect on HIV-1 replication - Bi, Mingyuan; Kang, Wen; Sun, Yongtao (Frontiers in Immunology, 2023)
Introduction: Heat shock protein (HSPs) are important intracellular factors, which are often involved in the regulation of viral replication including HIV-1 in infected individuals as molecular chaperone proteins. Heat shock proteins 70 (HSP70/HSPA) family play important roles in HIV replication, but this family contain many subtypes, and it is unclear how these subtypes participate in and affect HIV replication. Methods: To detect the interaction between HSPA14 and HspBP1 by CO-IP. Simulating HIV infection status in vitro to detect the change of intracellular HSPA14 expression after HIV infection in different cells. Constructing HSPA14 overexpression or knockdown cells to detect intracellular HIV replication levels after in vitro infection. Detecting the difference of HSPA expression levels in CD4+ T cells of untreated acute HIV-infected patients with different viral load. Results: In this study, we found that HIV infection can lead to changes in the transcriptional level of many HSPA subtypes, among which HSPA14 interacts with HIV transcriptional inhibitor HspBP1. The expression of HSPA14 in Jurkat and primary CD4+T cells infected with HIV were inhibited, overexpression of HSPA14 inhibited HIV replication, while knocking down HSPA14 promoted HIV replication. We also found that the expression level of HSPA14 is higher in peripheral blood CD4+T cells of untreated acute HIV infection patients with low viral load. Conclusion: HSPA14 is a potential HIV replication inhibitor and may restrict HIV replication by regulating the transcriptional inhibitor HspBP1. Further studies are needed to determine the specific mechanism by which HSPA14 regulates viral replication